Detection of abnormal aortic elastic properties in asymptomatic patients with Marfan syndrome by combined transoesophageal echocardiography and acoustic quantification. Issue 3 (March 1996) - Franke, A.; Mühler, E. G.; Klues, H. G.; Peters, K.; Lepper, W.; von Bernuth, G.; Hanrath, P.
Abstract : OBJECTIVE: To evaluate the potential value of transoesophageal echocardiography combined with automated border detection and acoustic quantification for the assessment of elastic properties of the thoracic aorta in patients with Marfan syndrome. SUBJECTS: 16 patients with Marfan syndrome and 12 age matched normal controls. METHODS: Transoesophageal echocardiography was performed in all subjects. Minimum and maximum diameters of the descending thoracic aorta were obtained from M mode images and acoustic quantification was used for the on-line evaluation of cross sectional aortic area and peak positive area changes over time. Compliance, distensibility, and stiffness index were calculated using M mode data and non-invasively measured blood pressure and were compared with the indices derived from acoustic quantification. RESULTS: Aortic dimensions normalised for body surface area were not statistically different between patients and normal controls, but there were significant differences for all elasticity indices except compliance. Marfan patients had a lower distensibility [4.2 (SD 1.8) v 5.8 (2.1) cm2/dyn, P < 0.05] and a higher stiffness index [9.7 (3.0) v 7.1 (1.8), P < 0.05]. The dynamic indices derived from the acoustic quantification were significantly smaller in Marfan patients [peak positive area change: 5.1 (1.0) v 7.7 (1.7) cm2/s; P < 0.001; and normalised peak positive area change: 2.5 (1.2) v 4.0 (0.8) cm2/s respectively, P < 0.001] and were suitable to discriminate between normal and abnormal elastic properties. CONCLUSIONS: In Marfan syndrome elastic properties of the descending aorta are significantly different from normal controls, even in the absence of vessel dilatation. In addition to established static indices, indices derived from acoustic quantification reflect dynamic changes of the cross sectional area for the evaluation of regional vessel mechanics. The on-line assessment of peak positive area change allows differentiation from normal individuals and may be more accurate than standard M mode measurements.